Perubahan Beberapa Sifat Fisika dan Kimia Ultisol Akibat Pemberian Pupuk Kompos Dan Kapur Dolomit pada Lahan Berteras - M. Rusli Alibasyah (Jurnal Floratek, 2016)
Changes of Some Physical and Chemical Ultisol Properties Given Compost Fertilizer and Dolomite Lime on Terraced Land ABSTRACT. This study aims to asses the changes of some physical and chemical ultisol properties  as a result of compost fertilizer and dolomite lime application on terraced land. This research using Randomize Block Design (RBD), consists of two factors, namely compost and dolomite lime. Parameters observed were physical and chemical properties of the soil. The results showed that compost has a very significant effect on the decrease of bulk density, the increase of total porosity, permeability, aggregate stability index, fast drainage pores, water available pores, soil water content at 2.54 pF, water content on 4.2 pF, the increase of P-available, and a significant affect on the slow drainage pores, the levels of C-organic, N-total, cation exchange capacity (CEC) and base saturation (BS). Dolomite lime has a very significant effect on bulk density, and a significant effect on the increase in total porosity, permeability, slow drainage pores, water available pores, N-total, CEC, BS,  and no significant effect on the aggregate stability index, fast drainage pores, water content at 4.54 pF and 4.2 pF ant the levels of C-organic. There also a very significant interaction between compost and dolomite lime on the increase in the pH of the soil.